An innovative method to characterize sorption-induced kerogen swelling in organic-rich shales. (15th October 2019) - Pang, Yu; He, Yongming; Chen, Shengnan
Abstract: Matrix swelling due to the gas sorption has not been properly accounted in the organic-rich shale formations. In general, the adsorbed gas attaches on the pore surface in the kerogen and clay minerals and occupies the pore volume. Meanwhile, the absorbed gas dissolves or diffuses into the matrix (solid lattice) of kerogen, resulting in the swelling of kerogen. As a result, the increase of the adsorbed and absorbed gases leads to a reduction of the pore volume for the free gas. Thus, it is essential to appropriately characterize the kerogen swelling caused by gas sorption so that to accurately determine the nanopore structure and the gas transport behavior in shale kerogen. In this study, an innovative method is developed to evaluate the swelling behavior of kerogen ascribed to the methane sorption. The method aims at characterizing the regions of adsorbed gas, absorbed gas, and free gas in the slit-shaped nanopores in shale kerogen based on the density profile determined using the Simplified Local-Density (SLD) model. Results for Barnett and Eagle Ford shale kerogens reveal that the gas adsorption prevails when the pore pressure is less than 6 MPa, whereas the gas absorption dominates the gas sorption process when the pore pressure is larger than 6 MPa. In addition, the ratio of absorption thickness to adsorption thickness increases with the pore pressure and such ratio reaches the 34.4% and 25.4% at the pore pressure around 20 MPa for the Barnett and Eagle Ford shale kerogens, respectively. Furthermore, the bulk and pore volumetric strains of the kerogen in the Barnett and Eagle Ford shale core samples are calculated based on the swelling length of kerogen caused by the methane sorption. The calculated strains of kerogen are in line with the measured strains of the shale and coal samples published in the literature, which verifies the reliability of the proposed innovative method. Finally, the impacts of methane sorption on the surface diffusion and the gas slippage in the slit nanopores of kerogen are also discussed. The proposed method provides a practical approach to characterize the sorption-induced kerogen swelling in shales, which is difficult to measure in the laboratory. The findings of this study advance the understanding of gas sorption process and give insight into the characterization of nanopore structure and gas transport mechanism in shale kerogen.